1929
DOI: 10.1002/ange.19290421904
|View full text |Cite
|
Sign up to set email alerts
|

Neuere Forschungen über Diffusion und elektrische Leitfähigkeit fester Salze

Abstract: Ubereinstimmung sind, und B e u t 1 e r und J os e p h y 2 4 ) konnten zeigen, dai3 diese Haufigkeit sehr empfindlich selbst kleinen Energiedifferenzen gegenuber ist. Dai3 bei Annaherung an genaue Obereinstimmung der Energie die Haufigkeit so zunimmt, dai3 der Wirkungsquerschnitt den gaskinetischen tatsachlich um Grofienordnungen ubertrifft, geht aus Versuchen v011 S c h u t z 2 5 ) , D a t t a ze) und neuerdings von B e u t -1 0 r 2 i ) hervor. Theoretisch wurde dieses Ergebnis von N o r d h s i m z 8 ) abgel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The conductivity values for the two-phase mixtures may as well exceed the conductivity values of the pure constituents. [29][30][31] Accordingly, the electrical properties of TiO 2 are supposedly only ameliorating.…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity values for the two-phase mixtures may as well exceed the conductivity values of the pure constituents. [29][30][31] Accordingly, the electrical properties of TiO 2 are supposedly only ameliorating.…”
Section: Resultsmentioning
confidence: 99%
“…Even ceria-based electrolytes, such as samaria-doped ceria (SDC) or gadolinia-doped ceria (GDC), with ionic conductivities of about 10 À2 S cm À1 at 600 C, present drawbacks due to their electronic properties under SOFC anode reducing atmosphere. The enhancement of the conductivity by adding a second phase in solid electrolytes is known since 1929 [15], but the research activity in this field began in 1973, where it was shown that the ionic conductivity of the solid electrolyte LiI was significantly increased by adding an inert second phase (Al 2 O 3 ) [16]. In recent years, combining ceramics with molten salts presents a growing interest for innovative high-temperature fuel cell applications.…”
Section: 4mentioning
confidence: 99%
“…The effect of conductivity enhancement by the addition of a second phase in solid electrolytes is known since 1929 [11].…”
Section: Introductionmentioning
confidence: 99%